Strategy of Economic Efficiency Enhancement for Land Use of Aviation Transport - Novakovska, І.; Stetsyuk, M.; Ischenko, N.; Skrypnyk, L. (Land Management, Cadastre and Land Monitoring, 2020)
The place and significance of land resources in the system of aviation transport have been researched. According to the analysis, aviation transport lands in the general structure of lands do not occupy significant positions (II cluster). But, if used effectively, these lands can be a factor in improving the financial performance of airports. It is shown that an important role in land use play economic levers as a set of assets that operate in the economic plane and operate for economic purposes. The possibilities and potential of economic instruments of regulation and characteristics of institutional support for the implementation of economic levers are research. The priorities of economic influence on the possibilities of use and protection of land of aviation transport have been formed. It is shown that it is important to account the interests of stakeholders and the ability of an objective approach to regulation when formulating land use policies.Keywords: land resources, air transport, economic tools, priorities of impact.